Physicochemical properties of grain of promising winter durum wheat varieties and lines in the south of the Rostov region - A. S. Ivanisova; D. M. Marchenko; O. A. Dubinina; L. I. Maidaburo; N. S. Kravchenko (Зерновое хозяйство России)
The most important thing in the production of durum wheat is to obtain high-quality grain. In this regard, in the Rostov Region, there has been studied the physical and chemical properties of this crop and identiﬁed several sources for high-quality grain breeding. The objects of study were 30 winter durum wheat varieties and lines of our own breeding, with the standard variety ‘Kristella’. Large grain (1000-grain weight over 40 g) was formed by 12 winter durum wheat samples. According to the GOST, 26 varieties and lines (770–809 g/l) belonged to the 1st class of grain. In 2021–2023, grain hardness varied from 69 % to 93 %. This trait was inﬂuenced by weather conditions during the years of study, grain with large hardness (100 %) was formed in the favorable 2022, in 2023 the grain was ﬂoury (51 %). The protein percentage in grain varied over the years from 13.70% in 2022 to 14.91 % in 2021. The mean gluten content of winter durum wheat samples was consistently high over the years and ranged from 28.0 % (2022) to 30.1 % (2021). The mean carotenoid content over the years varied signiﬁcantly from 472 μg/% (2023) to 718 μg/% (2021). There were signiﬁcant ﬂuctuations among the samples. Due to the diversity of weather conditions during the years of study, there have been identiﬁed 6 winter durum wheat varieties and lines ‘Diona’, ‘Dinas’, ‘Pridonie’, ‘691/20’, ‘390/20’, ‘1377/20’ according to the complex of physical and chemical properties.